Effects of Sigatoka leaf spot (Mycosphaerella musicola Leach)on fruit yields, field ripening and greenlife of bananas in North Queensland - Ramsey, M.D.; Daniells, J.W.; Anderson, V.J.
The effects of a range of leaf-spot severities on bunch weight, percent field ripening and greenlife of bananas cultivar 'Williams' were determined in North Queensland. Disease and yield parameters were assessed on individual plants at harvest. The 'nurse-sucker' technique was used to manage the cropping cycle and eliminate disease carry-over between crops, and a gradation of disease severities was maintained with eight fungicide treatments. There was a linear relationship (r2=0.95)between leaf-spot severity and the number of viable leaves at harvest. Bunch weight increased logistically with increasing leaf number (R2=0.98). Plants with fewer than five viable leaves at harvest produced lighter bunches. Lower yields were due to reduced fruit weight, not to fewer hands of bananas. The percentage of field-ripened bunches decreased logistically as leaf number increased (R2=0.92). All bunches from plants with fewer than four leaves were field-ripe. However, some field ripening occurred on plants with up to 10 leaves, which reduced marketable yields. There was a quadratic relationship between greenlife of fruit from unripened bunches and leaf number (R2=0.92). More than 10 leaves at harvest were necessary to obtain optimal yield of marketable fruit, which corresponded with the tenth leaf being the youngest leaf spotted at bunch emergence.
Keywords: BANANA; MUSA; MYCOSPHAERELLA MUSICOLA LEACH; QUALITY; YIELD